Application of Green Technologies to Reduce Impacts of Urban Non-Point Sources Pollution - Gurung, Sher Bahadur; Geronimo, Franz Kevin F.; Hong, Jungsun; Kim, Lee-Hyung (Kathford Journal of Engineering and Management, 2023)
Storm water runoff from different types of urban catchments and discharge from LID system applied in urban catchments were monitored since 2009 to 2017 in Kongju National University. The performance of green technology (GI) system was evaluated to mitigate the problem like pollutant treatment and restore natural hydrological cycle. The result showed that the urban catchments were sources of pollutants like sediments, organics, nutrients and heavy metals. Thus, the concentrations of these pollutants are highly dependent on the antecedent dry days and types of catchments. Since, roads and parking lots observed higher concentration of sediment and organics however heavy metals were highly contributed by the rooftop areas. Moreover, the application of green technologies could be a better solution to mitigate the problems associated with urbanization. Similarly, GI technology were highly significant to reduce runoff generated and can restore natural hydrological cycle. Lastly, the pollutant removal efficiency of different system was significant due to application of different media and plants.